Photocatalysis with organic dyes: facile access to reactive intermediates for synthesis - Amos, Stephanie G. E.; Garreau, Marion; Buzzetti, Luca; Waser, Jerome (Beilstein Journal of Organic Chemistry, 2020)
Organic dyes have emerged as a reliable class of photoredox catalysts. Their great structural variety combined with the easy fine-tuning of their electronic properties has unlocked new possibilities for the generation of reactive intermediates. In this review, we provide an overview of the available approaches to access reactive intermediates that employ organophotocatalysis. Our contribution is not a comprehensive description of the work in the area but rather focuses on key concepts, accompanied by a few selected illustrative examples. The review is organized along the type of reactive intermediates formed in the reaction, including C(sp3) and C(sp2) carbon-, nitrogen-, oxygen-, and sulfur-centered radicals, open-shell charged species, and sensitized organic compounds.
Keywords: organic dyes; photocatalysis; photoredox catalysis; radicals; reactive intermediates

(untitled) - Nicewicz, D. A.; MacMillan, D. W. C. (Science, 2008)

(untitled) - Ischay, M. A.; Anzovino, M. E.; Du, J.; Yoon, T. P. (J. Am. Chem. Soc., 2008)

(untitled) - Narayanam, J. M. R.; Tucker, J. W.; Stephenson, C. R. J. (J. Am. Chem. Soc., 2009)

(untitled) - Ravelli, D.; Dondi, D.; Fagnoni, M.; Albini, A. (Chem. Soc. Rev., 2009)

(untitled) - Ciamician, G.; Silber, P. (Ber. Dtsch. Chem. Ges., 1908)

(untitled) - Ciamician, G. (Science, 1912)

(untitled) - Juris, A.; Balzani, V.; Barigelletti, F.; Campagna, S.; Belser, P.; von Zelewsky, A. (Coord. Chem. Rev., 1988)

(untitled) - Yoon, T. P.; Ischay, M. A.; Du, J. (Nat. Chem., 2010)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Shaw, M. H.; Twilton, J.; MacMillan, D. W. C. (J. Org. Chem., 2016)

(untitled) - Ravelli, D.; Protti, S.; Fagnoni, M. (Chem. Rev., 2016)

(untitled) - Arias-Rotondo, D. M.; McCusker, J. K. (Chem. Soc. Rev., 2016)

(untitled) - Zhang, X.; Li, Y.; Hao, X.; Jin, K.; Zhang, R.; Duan, C. (Tetrahedron, 2018)

(untitled) - Selsted, M. E.; Becker, H. W., III (Anal. Biochem., 1986)

(untitled) - Neckers, D. C. (J. Photochem. Photobiol., A, 1989)

(untitled) - Romero, N. A.; Nicewicz, D. A. (Chem. Rev., 2016)

(untitled) - Pitre, S. P.; McTiernan, C. D.; Scaiano, J. C. (ACS Omega, 2016)

Photoorganocatalysis in organic synthesis - Fagnoni, M.; Protti, S.; Ravelli, D. (World Scientific, 2019)

(untitled) - Ravelli, D.; Fagnoni, M.; Albini, A. (Chem. Soc. Rev., 2013)

(untitled) - Hari, D. P.; König, B. (Chem. Commun., 2014)

(untitled) - Joshi-Pangu, A.; Lévesque, F.; Roth, H. G.; Oliver, S. F.; Campeau, L.-C.; Nicewicz, D.; DiRocco, D. A. (J. Org. Chem., 2016)

(untitled) - Sideri, I. K.; Voutyritsa, E.; Kokotos, C. G. (Org. Biomol. Chem., 2018)

(untitled) - Shang, T.-Y.; Lu, L.-H.; Cao, Z.; Liu, Y.; He, W.-M.; Yu, B. (Chem. Commun., 2019)

(untitled) - White, A.; Wang, L.; Nicewicz, D. (Synlett, 2019)

(untitled) - Zilate, B.; Fischer, C.; Sparr, C. (Chem. Commun., 2020)

Principles and applications of photochemistry - Wardle, B. (John Wiley & Sons, 2009)

Photochemistry of Organic Compounds - Klán, P.; Wirz, J. (John Wiley and Sons, 2011)

Photochemistry and photophysics: concepts, research, applications - Balzani, V.; Ceroni, P.; Juris, A. (Wiley-VCH, 2014)

(untitled) - Twilton, J.; Le, C.; Zhang, P.; Shaw, M. H.; Evans, R. W.; MacMillan, D. W. C. (Nat. Rev. Chem., 2017)

(untitled) - Wang, C.-S.; Dixneuf, P. H.; Soulé, J.-F. (Chem. Rev., 2018)

(untitled) - Romero, K. J.; Galliher, M. S.; Pratt, D. A.; Stephenson, C. R. J. (Chem. Soc. Rev., 2018)

(untitled) - Yi, H.; Zhang, G.; Wang, H.; Huang, Z.; Wang, J.; Singh, A. K.; Lei, A. (Chem. Rev., 2017)

(untitled) - Kolbe, H. (Ann. Chem. Pharm., 1849)

(untitled) - Vijh, A. K.; Conway, B. E. (Chem. Rev., 1967)

(untitled) - Hunsdiecker, H.; Hunsdiecker, C. (Ber. Dtsch. Chem. Ges. B, 1942)

(untitled) - Barton, D. H. R.; Dowlatshahi, H. A.; Motherwell, W. B.; Villemin, D. (J. Chem. Soc., Chem. Commun., 1980)

(untitled) - Barton, D. H. R.; Crich, D.; Motherwell, W. B. (Tetrahedron Lett., 1983)

(untitled) - Barton, D. H. R.; Crich, D.; Motherwell, W. B. (J. Chem. Soc., Chem. Commun., 1983)

(untitled) - Xuan, J.; Zhang, Z.-G.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Huang, H.; Jia, K.; Chen, Y. (ACS Catal., 2016)

(untitled) - Griffin, J. D.; Zeller, M. A.; Nicewicz, D. A. (J. Am. Chem. Soc., 2015)

(untitled) - Marcote, D. C.; Street-Jeakings, R.; Dauncey, E.; Douglas, J. J.; Ruffoni, A.; Leonori, D. (Org. Biomol. Chem., 2019)

(untitled) - Zhang, M.-J.; Schroeder, G. M.; He, Y.-H.; Guan, Z. (RSC Adv., 2016)

(untitled) - Horner, L.; Jordan, M. (Justus Liebigs Ann. Chem., 1978)

(untitled) - Schwarz, J.; König, B. (Green Chem., 2016)

(untitled) - Tlahuext-Aca, A.; Candish, L.; Garza-Sanchez, R. A.; Glorius, F. (ACS Catal., 2018)

(untitled) - Jia, J.; Lefebvre, Q.; Rueping, M. (Org. Chem. Front., 2020)

(untitled) - Yoshida, J.-i.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Gutiérrez-Bonet, Á.; Tellis, J. C.; Matsui, J. K.; Vara, B. A.; Molander, G. A. (ACS Catal., 2016)

(untitled) - Patel, N. R.; Kelly, C. B.; Siegenfeld, A. P.; Molander, G. A. (ACS Catal., 2017)

(untitled) - Matsui, J. K.; Primer, D. N.; Molander, G. A. (Chem. Sci., 2017)

(untitled) - Mateos, J.; Rigodanza, F.; Vega‐Peñaloza, A.; Sartorel, A.; Natali, M.; Bortolato, T.; Pelosi, G.; Companyó, X.; Bonchio, M.; Dell'Amico, L. (Angew. Chem., Int. Ed., 2020)

(untitled) - Neumann, M.; Füldner, S.; König, B.; Zeitler, K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Martinez-Haya, R.; Miranda, M. A.; Marin, M. L. (Eur. J. Org. Chem., 2017)

(untitled) - Lee, J.; Papatzimas, J. W.; Bromby, A. D.; Gorobets, E.; Derksen, D. J. (RSC Adv., 2016)

(untitled) - Capaldo, L.; Ravelli, D. (Eur. J. Org. Chem., 2017)

(untitled) - Shen, Y.; Gu, Y.; Martin, R. (J. Am. Chem. Soc., 2018)

(untitled) - Xia, J.-B.; Zhu, C.; Chen, C. (J. Am. Chem. Soc., 2013)

(untitled) - Fan, X.-Z.; Rong, J.-W.; Wu, H.-L.; Zhou, Q.; Deng, H.-P.; Tan, J. D.; Xue, C.-W.; Wu, L.-Z.; Tao, H.-R.; Wu, J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Loh, Y. Y.; Nagao, K.; Hoover, A. J.; Hesk, D.; Rivera, N. R.; Colletti, S. L.; Davies, I. W.; MacMillan, D. W. C. (Science, 2017)

(untitled) - McGlacken, G. P.; Bateman, L. M. (Chem. Soc. Rev., 2009)

(untitled) - Bonin, H.; Sauthier, M.; Felpin, F.-X. (Adv. Synth. Catal., 2014)

(untitled) - Sandmeyer, T. (Ber. Dtsch. Chem. Ges., 1884)

(untitled) - Gomberg, M.; Bachmann, W. E. (J. Am. Chem. Soc., 1924)

(untitled) - Meerwein, H.; Büchner, E.; van Emster, K. (J. Prakt. Chem., 1939)

(untitled) - Galli, C. (Chem. Rev., 1988)

(untitled) - Fry, A. J.; Krieger, R. L. (J. Org. Chem., 1976)

(untitled) - Ghosh, I.; Marzo, L.; Das, A.; Shaikh, R.; König, B. (Acc. Chem. Res., 2016)

(untitled) - Sheng, M.; Frurip, D.; Gorman, D. (J. Loss Prev. Process Ind., 2015)

(untitled) - Filimonov, V. D.; Krasnokutskaya, E. A.; Kassanova, A. Z.; Fedorova, V. A.; Stankevich, K. S.; Naumov, N. G.; Bondarev, A. A.; Kataeva, V. A. (Eur. J. Org. Chem., 2019)

(untitled) - Andrieux, C. P.; Pinson, J. (J. Am. Chem. Soc., 2003)

(untitled) - Raicopol, M.; Necula, L.; Ionita, M.; Pilan, L. (Surf. Interface Anal., 2012)

(untitled) - Hari, D. P.; Schroll, P.; König, B. (J. Am. Chem. Soc., 2012)

(untitled) - Vidyacharan, S.; Ramanjaneyulu, B. T.; Jang, S.; Kim, D.-P. (ChemSusChem, 2019)

(untitled) - de Souza, A. A. N.; Silva, N. S.; Müller, A. V.; Polo, A. S.; Brocksom, T. J.; de Oliveira, K. T. (J. Org. Chem., 2018)

(untitled) - Gong, X.; Li, X.; Xie, W.; Wu, J.; Ye, S. (Org. Chem. Front., 2019)

(untitled) - Pause, L.; Robert, M.; Savéant, J.-M. (J. Am. Chem. Soc., 1999)

(untitled) - Roth, H.; Romero, N.; Nicewicz, D. (Synlett, 2016)

(untitled) - Wang, L.; Byun, J.; Li, R.; Huang, W.; Zhang, K. A. I. (Adv. Synth. Catal., 2018)

(untitled) - Garrido-Castro, A. F.; Salaverri, N.; Maestro, M. C.; Alemán, J. (Org. Lett., 2019)

(untitled) - Ghosh, I.; Ghosh, T.; Bardagi, J. I.; König, B. (Science, 2014)

(untitled) - Shaikh, R. S.; Düsel, S. J. S.; König, B. (ACS Catal., 2016)

(untitled) - Neumeier, M.; Sampedro, D.; Májek, M.; de la Peña O'Shea, V. A.; Jacobi von Wangelin, A.; Pérez-Ruiz, R. (Chem. – Eur. J., 2018)

(untitled) - Kim, H.; Kim, H.; Lambert, T. H.; Lin, S. (J. Am. Chem. Soc., 2020)

(untitled) - Gu, L.; Jin, C.; Liu, J.; Ding, H.; Fan, B. (Chem. Commun., 2014)

(untitled) - Gu, L.; Jin, C.; Wang, W.; He, Y.; Yang, G.; Li, G. (Chem. Commun., 2017)

(untitled) - Aukland, M. H.; Šiaučiulis, M.; West, A.; Perry, G. J. P.; Procter, D. J. (Nat. Catal., 2020)

(untitled) - Raviola, C.; Protti, S.; Ravelli, D.; Fagnoni, M. (Green Chem., 2019)

(untitled) - Shi, Q.; Li, P.; Zhu, X.; Wang, L. (Green Chem., 2016)

(untitled) - Capaldo, L.; Riccardi, R.; Ravelli, D.; Fagnoni, M. (ACS Catal., 2018)

(untitled) - Alandini, N.; Buzzetti, L.; Favi, G.; Schulte, T.; Candish, L.; Collins, K. D.; Melchiorre, P. (Angew. Chem., Int. Ed., 2020)

(untitled) - Tripathi, S.; Kapoor, R.; Yadav, L. D. S. (Adv. Synth. Catal., 2018)

(untitled) - Arnold, D. R.; Lamont, L. J. (Can. J. Chem., 1989)

(untitled) - Arnold, D. R.; Du, X.; Chen, J. (Can. J. Chem., 1995)

(untitled) - Holy, N. L.; Marcum, J. D. (Angew. Chem., Int. Ed. Engl., 1971)

(untitled) - Romero, N. A.; Nicewicz, D. A. (J. Am. Chem. Soc., 2014)

(untitled) - Margrey, K. A.; Nicewicz, D. A. (Acc. Chem. Res., 2016)

(untitled) - Hamilton, D. S.; Nicewicz, D. A. (J. Am. Chem. Soc., 2012)

(untitled) - Wilger, D. J.; Grandjean, J.-M. M.; Lammert, T. R.; Nicewicz, D. A. (Nat. Chem., 2014)

(untitled) - Wang, H.; Lu, Q.; Chiang, C.-W.; Luo, Y.; Zhou, J.; Wang, G.; Lei, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Mukaiyama, T.; Sato, T.; Hanna, J. (Chem. Lett., 1973)

(untitled) - McMurry, J. E.; Fleming, M. P. (J. Am. Chem. Soc., 1974)

(untitled) - Nakajima, M.; Fava, E.; Loescher, S.; Jiang, Z.; Rueping, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Gualandi, A.; Rodeghiero, G.; Della Rocca, E.; Bertoni, F.; Marchini, M.; Perciaccante, R.; Jansen, T. P.; Ceroni, P.; Cozzi, P. G. (Chem. Commun., 2018)

(untitled) - Tarantino, K. T.; Liu, P.; Knowles, R. R. (J. Am. Chem. Soc., 2013)

(untitled) - Trowbridge, A.; Reich, D.; Gaunt, M. J. (Nature, 2018)

(untitled) - Fuentes de Arriba, A. L.; Urbitsch, F.; Dixon, D. J. (Chem. Commun., 2016)

(untitled) - Du, J.; Skubi, K. L.; Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Ma, J.; Rosales, A. R.; Huang, X.; Harms, K.; Riedel, R.; Wiest, O.; Meggers, E. (J. Am. Chem. Soc., 2017)

(untitled) - Romero, N. A.; Margrey, K. A.; Tay, N. E.; Nicewicz, D. A. (Science, 2015)

(untitled) - Margrey, K. A.; McManus, J. B.; Bonazzi, S.; Zecri, F.; Nicewicz, D. A. (J. Am. Chem. Soc., 2017)

(untitled) - Margrey, K. A.; Levens, A.; Nicewicz, D. A. (Angew. Chem., Int. Ed., 2017)

(untitled) - McManus, J. B.; Nicewicz, D. A. (J. Am. Chem. Soc., 2017)

(untitled) - Tay, N. E. S.; Nicewicz, D. A. (J. Am. Chem. Soc., 2017)

(untitled) - Chen, W.; Huang, Z.; Tay, N. E. S.; Giglio, B.; Wang, M.; Wang, H.; Wu, Z.; Nicewicz, D. A.; Li, Z. (Science, 2019)

(untitled) - Holmberg-Douglas, N.; Nicewicz, D. A. (Org. Lett., 2019)

(untitled) - Bonesi, S. M.; Fagnoni, M. (Chem. – Eur. J., 2010)

(untitled) - Chen, M.; Zhao, X.; Yang, C.; Xia, W. (Org. Lett., 2017)

(untitled) - Chatterjee, A.; König, B. (Angew. Chem., Int. Ed., 2019)

(untitled) - Mizuno, K.; Ikeda, M.; Otsuji, Y. (Tetrahedron Lett., 1985)

(untitled) - Tsujimoto, K.; Nakao, N.; Ohashi, M. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Arceo, E.; Jurberg, I. D.; Álvarez-Fernández, A.; Melchiorre, P. (Nat. Chem., 2013)

(untitled) - Crisenza, G. E. M.; Mazzarella, D.; Melchiorre, P. (J. Am. Chem. Soc., 2020)

(untitled) - Zard, S. Z. (Chem. Soc. Rev., 2008)

(untitled) - Xiong, T.; Zhang, Q. (Chem. Soc. Rev., 2016)

(untitled) - Chen, J.-R.; Hu, X.-Q.; Lu, L.-Q.; Xiao, W.-J. (Chem. Soc. Rev., 2016)

(untitled) - Kärkäs, M. D. (ACS Catal., 2017)

(untitled) - Davies, J.; Morcillo, S. P.; Douglas, J. J.; Leonori, D. (Chem. – Eur. J., 2018)

(untitled) - Zhao, Y.; Xia, W. (Chem. Soc. Rev., 2018)

(untitled) - Stateman, L.; Nakafuku, K.; Nagib, D. (Synthesis, 2018)

(untitled) - Jiang, H.; Studer, A. (Chem. Soc. Rev., 2020)

(untitled) - Kumar, G.; Pradhan, S.; Chatterjee, I. (Chem. – Asian J., 2020)

(untitled) - Horner, J. H.; Musa, O. M.; Bouvier, A.; Newcomb, M. (J. Am. Chem. Soc., 1998)

(untitled) - Davies, J.; Svejstrup, T. D.; Fernandez Reina, D.; Sheikh, N. S.; Leonori, D. (J. Am. Chem. Soc., 2016)

(untitled) - Morcillo, S. P.; Dauncey, E. M.; Kim, J. H.; Douglas, J. J.; Sheikh, N. S.; Leonori, D. (Angew. Chem., Int. Ed., 2018)

(untitled) - Walton, J. (Molecules, 2016)

(untitled) - Shi, L.; Xia, W. (Chem. Soc. Rev., 2012)

(untitled) - Hu, J.; Wang, J.; Nguyen, T. H.; Zheng, N. (Beilstein J. Org. Chem., 2013)

(untitled) - Jiang, H.; Studer, A. (CCS Chem., 2019)

(untitled) - Davies, J.; Booth, S. G.; Essafi, S.; Dryfe, R. A. W.; Leonori, D. (Angew. Chem., Int. Ed., 2015)

(untitled) - Davies, J.; Sheikh, N. S.; Leonori, D. (Angew. Chem., Int. Ed., 2017)

(untitled) - Jiang, H.; Studer, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Dauncey, E. M.; Morcillo, S. P.; Douglas, J. J.; Sheikh, N. S.; Leonori, D. (Angew. Chem., Int. Ed., 2018)

(untitled) - Le Vaillant, F.; Garreau, M.; Nicolai, S.; Gryn'ova, G.; Corminboeuf, C.; Waser, J. (Chem. Sci., 2018)

(untitled) - Tian, W.-F.; Wang, D.-P.; Wang, S.-F.; He, K.-H.; Cao, X.-P.; Li, Y. (Org. Lett., 2018)

(untitled) - Pandey, G.; Laha, R. (Angew. Chem., Int. Ed., 2015)

(untitled) - Chen, H.; Guo, L.; Yu, S. (Org. Lett., 2018)

(untitled) - Moon, Y.; Park, B.; Kim, I.; Kang, G.; Shin, S.; Kang, D.; Baik, M.-H.; Hong, S. (Nat. Commun., 2019)

(untitled) - Jiang, H.; Studer, A. (Angew. Chem., Int. Ed., 2018)

(untitled) - Hari, D. P.; König, B. (Org. Lett., 2011)

(untitled) - Condie, A. G.; González-Gómez, J. C.; Stephenson, C. R. J. (J. Am. Chem. Soc., 2010)

(untitled) - Pan, Y.; Kee, C. W.; Chen, L.; Tan, C.-H. (Green Chem., 2011)

(untitled) - Xuan, J.; Xia, X.-D.; Zeng, T.-T.; Feng, Z.-J.; Chen, J.-R.; Lu, L.-Q.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Muriel, B.; Gagnebin, A.; Waser, J. (Chem. Sci., 2019)

(untitled) - Garreau, M.; Le Vaillant, F.; Waser, J. (Angew. Chem., Int. Ed., 2019)

(untitled) - Hu, X.-Q.; Chen, J.; Chen, J.-R.; Yan, D.-M.; Xiao, W.-J. (Chem. – Eur. J., 2016)

(untitled) - Guo, J.-J.; Hu, A.; Zuo, Z. (Tetrahedron Lett., 2018)

(untitled) - Capaldo, L.; Ravelli, D. (Chem. Commun., 2019)

(untitled) - Wu, X.; Zhu, C. (Chem. Commun., 2019)

(untitled) - Kim, I.; Park, B.; Kang, G.; Kim, J.; Jung, H.; Lee, H.; Baik, M.-H.; Hong, S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Kim, Y.; Lee, K.; Mathi, G. R.; Kim, I.; Hong, S. (Green Chem., 2019)

(untitled) - Quint, V.; Morlet-Savary, F.; Lohier, J.-F.; Lalevée, J.; Gaumont, A.-C.; Lakhdar, S. (J. Am. Chem. Soc., 2016)

(untitled) - Devari, S.; Rizvi, M. A.; Shah, B. A. (Tetrahedron Lett., 2016)

(untitled) - Zhu, X.; Xie, X.; Li, P.; Guo, J.; Wang, L. (Org. Lett., 2016)

(untitled) - Li, J.; Zhang, J.; Tan, H.; Wang, D. Z. (Org. Lett., 2015)

(untitled) - Dénès, F.; Pichowicz, M.; Povie, G.; Renaud, P. (Chem. Rev., 2014)

(untitled) - Glass, R. S. (Top. Curr. Chem., 2018)

(untitled) - Zubkov, M. O.; Kosobokov, M. D.; Levin, V. V.; Kokorekin, V. A.; Korlyukov, A. A.; Hu, J.; Dilman, A. D. (Chem. Sci., 2020)

(untitled) - Limnios, D.; Kokotos, C. G. (Adv. Synth. Catal., 2017)

(untitled) - Guerrero-Corella, A.; Martinez-Gualda, A. M.; Ahmadi, F.; Ming, E.; Fraile, A.; Alemán, J. (Chem. Commun., 2017)

(untitled) - Zalesskiy, S. S.; Shlapakov, N. S.; Ananikov, V. P. (Chem. Sci., 2016)

(untitled) - Chaudhary, R.; Natarajan, P. (ChemistrySelect, 2017)

(untitled) - Zhao, Y.; Gong, H.; Jiang, K.; Yan, S.; Lin, J.; Chen, M. (Macromolecules, 2018)

(untitled) - Hell, S. M.; Meyer, C. F.; Laudadio, G.; Misale, A.; Willis, M. C.; Noël, T.; Trabanco, A. A.; Gouverneur, V. (J. Am. Chem. Soc., 2020)

(untitled) - Yang, W.; Yang, S.; Li, P.; Wang, L. (Chem. Commun., 2015)

(untitled) - Huang, M.-H.; Zhu, Y.-L.; Hao, W.-J.; Wang, A.-F.; Wang, D.-C.; Liu, F.; Wei, P.; Tu, S.-J.; Jiang, B. (Adv. Synth. Catal., 2017)

(untitled) - Storozhenko, O. A.; Festa, A. A.; Detistova, G. I.; Rybakov, V. B.; Varlamov, A. V.; Van der Eycken, E. V.; Voskressensky, L. G. (J. Org. Chem., 2020)

(untitled) - Zhang, G.; Zhang, L.; Yi, H.; Luo, Y.; Qi, X.; Tung, C.-H.; Wu, L.-Z.; Lei, A. (Chem. Commun., 2016)

(untitled) - Ghogare, A. A.; Greer, A. (Chem. Rev., 2016)

(untitled) - Metternich, J. B.; Gilmour, R. (J. Am. Chem. Soc., 2015)

(untitled) - Livingstone, K.; Tenberge, M.; Pape, F.; Daniliuc, C. G.; Jamieson, C.; Gilmour, R. (Org. Lett., 2019)

(untitled) - Faßbender, S. I.; Molloy, J. J.; Mück‐Lichtenfeld, C.; Gilmour, R. (Angew. Chem., Int. Ed., 2019)

(untitled) - Onneken, C.; Bussmann, K.; Gilmour, R. (Angew. Chem., Int. Ed., 2020)

(untitled) - Cai, W.; Fan, H.; Ding, D.; Zhang, Y.; Wang, W. (Chem. Commun., 2017)

(untitled) - Lu, J.; Pattengale, B.; Liu, Q.; Yang, S.; Shi, W.; Li, S.; Huang, J.; Zhang, J. (J. Am. Chem. Soc., 2018)

(untitled) - Alonso, R.; Bach, T. (Angew. Chem., Int. Ed., 2014)

(untitled) - Kumarasamy, E.; Raghunathan, R.; Jockusch, S.; Ugrinov, A.; Sivaguru, J. (J. Am. Chem. Soc., 2014)

(untitled) - Mojr, V.; Svobodová, E.; Straková, K.; Neveselý, T.; Chudoba, J.; Dvořáková, H.; Cibulka, R. (Chem. Commun., 2015)

(untitled) - Silvi, M.; Melchiorre, P. (Nature, 2018)

(untitled) - Bottecchia, C.; Noël, T. (Chem. – Eur. J., 2019)

(untitled) - Capaldo, L.; Quadri, L. L.; Ravelli, D. (Angew. Chem., Int. Ed., 2019)

(untitled) - Yu, Y.; Guo, P.; Zhong, J.-S.; Yuan, Y.; Ye, K.-Y. (Org. Chem. Front., 2020)